2017
DOI: 10.1016/j.bjm.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of Pseudomonas fluorescens growth under different temperature and pH values

Abstract: Meat is one of the most perishable foods owing to its nutrient availability, high water activity, and pH around 5.6. These properties are highly conducive for microbial growth. Fresh meat, when exposed to oxygen, is subjected to the action of aerobic psychrotrophic, proteolytic, and lipolytic spoilage microorganisms, such as Pseudomonas spp. The spoilage results in the appearance of slime and off-flavor in food. In order to predict the growth of Pseudomonas fluorescens in fresh meat at different pH values, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…Pseudomonas fluorescens is another psychrotrophic bacterium responsible for causing meat spoilage (Gonçalves, Piccoli, Peres, & Saúde, 2017). Some strains of P. fluorescens isolated from petroleum hydrocarbon-contaminated soil have shown the ability to utilize a diverse range of hydrocarbon sources (Barathi & Vasudevan, 2001).…”
Section: Pseudomonas Fluorescensmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas fluorescens is another psychrotrophic bacterium responsible for causing meat spoilage (Gonçalves, Piccoli, Peres, & Saúde, 2017). Some strains of P. fluorescens isolated from petroleum hydrocarbon-contaminated soil have shown the ability to utilize a diverse range of hydrocarbon sources (Barathi & Vasudevan, 2001).…”
Section: Pseudomonas Fluorescensmentioning
confidence: 99%
“…readily form biofilms under the chilled conditions used in the meat industry. Studies have indicated that the slime layer that grows on the surface of low‐temperature stored meat during spoilage is in fact a biofilm (Gonçalves et al., ; Jay, Vilai, & Hughes, ). The layer of slime formed on spoiled meat surfaces is composed of bacterial biofilm and meat exudate.…”
Section: Pseudomonas Biofilmsmentioning
confidence: 99%
“…Nevertheless, the contamination of Pseudomonas in other meat products should not be ignored. The ability of these microorganisms to grow under refrigeration temperatures is a challenge that should be counteracted [37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…2) Development, v. 9, n. 7, e162973858, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.3858 significativamente influenciou a taxa de inibição desta bactéria. Gonçalves et al (2017) também verificaram que o pH foi o parâmetro que mais influenciou para inibição do crescimento de Pseudomonas fluorescens em caldo de carne, sendo quanto menor o pH menores os valores de taxa máxima de crescimento.…”
Section: Influência Dos Parâmetros No Crescimento Das Bactérias Patogunclassified
“…Ao longo dos anos vários pesquisadores têm utilizado a microbiologia preditiva para avaliar o comportamento de bactérias patogênicas como Escherichia coli, Pseudomonas fluorescens, Listeria monocytogenes, Salmonella, Aeromonas, bactérias ácidos láticas e Enterobacteriaceae frente à parâmetros tais como: pH, temperatura, atividade de água, ácido acético, ácido propiônico, cloreto de sódio, dióxido de carbono, dentre outros (Akkermans et al, 2018;Couvert et al, 2017;Nyhan et al, 2018;Gonçalves et al, 2017;Hoel et al, 2018;Iliadis et al, 2018). Alguns pesquisadores têm realizado estudos preditivos de inibição bacteriana utilizando extratos de plantas como antimicrobianos naturais, dentre eles pode-se citar Krishnan et al (2015), os quais avaliaram o efeito de extratos de cravo da índia, canela e Research, Society and Development, v. 9, n. 7, e162973858, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.3858 orégano no crescimento de bactérias ácidos láticas e Enterobacteriaceae nas temperaturas 4, 10, 15 e 20°C, obtendo-se bons ajustes pelo modelo de Gompertz.…”
Section: Introductionunclassified